Choosing antithrombotics for atrial fibrillation in primary care - Mustafa, M; Sheppard, JP (Royal College of General Practictioners, 2020)
Atrial fibrillation (AF) is the most common cardiac arrhythmia in the UK affecting 1.3 million people. AF is particularly common in older people, with one in ten over the age of 75 years affected. The prevalence of AF is projected to increase with improved survival of patients from chronic cardiac disorders that predispose to AF, such as coronary heart disease. AF increases the risk of stroke fivefold due to thromboembolism and cause 15% of all strokes.